ANTIOXIDANT ACTIVITIES USING DPPH, FIC, FRAP, AND ABTS METHODS FROM ETHANOLIC EXTRACT OF LEMPUYANG GAJAH RHIZOME (Zingiber zerumbet (L.) Roscoeex Sm.) - Jamilatur Rohmah (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2022)
One of the Zingiber species that has long been used as traditional medicine by local Indonesian people is lempuyang (Zingiber ssp.). In its use as traditional medicine, it is more often used than other types of lempuyang, namely the lempuyang gajah (Zingiber zerumbet (L.) Roscoeex Sm.). Therefore, this study focused on the Zingiber zerumbet (L.) Roscoeex Sm. Most of the biological activities reported for this plant are attributed to phenolic contents and volatile principles. Hence, a detailed investigation of antioxidant activity, flavonoid, and phenolic content of Zingiber zerumbet (L.) Roscoeex Sm. rhizome was carried out. The purpose of this study was to determine the total flavonoid, phenolic, and antioxidant activity of Zingiber zerumbet (L.) Roscoeex Sm. extract in several methods of reducing free radicals DPPH, FIC, FRAP, and ABTS. The extraction method used is maceration extraction with 70% ethanol solvent and concentrated. The total phenolic content was determined by the Folin-Ciocalteu method with gallic acid as the standard, while the total flavonoid content was determined by the quercetin method. Ascorbic acid was used as a positive control of antioxidant activity. The Zingiber zerumbet (L.) Roscoeex Sm. plant used was obtained from the village of Tegal Bulu Banyuwangi. This type of research is an experimental study with the concentration of the extract used, namely 20, 40, 60, 80, and 100 mg/L. The results showed that the ethanol extract of Zingiber zerumbet (L.) Roscoeex Sm. rhizome contained total phenolic and flavonoid content of 23.58±0.25 mgGAE/g and 12.21±0.03 QUE/g extract, respectively. Antioxidant activity with IC50 value in the DPPH free radical reduction method of 11.40 ± 0.23 which is included in the very strong category, FIC of 121.46±2.93 which is included in the medium category, FRAP of 19.38±0.14 which is included in the very strong category, and ABTS of 89.32±0.15 which is included in the strong category. Phenolics and flavonoids are thought to have an important role in the antioxidant activity of Zingiber zerumbet (L.) Roscoeex Sm. rhizome.